Comprehensive Metabolomic Profiling of Cord Blood and Placental Tissue in Surviving Monochorionic Twins Complicated by Twin-Twin Transfusion Syndrome With or Without Fetoscopic Laser Coagulation Surgery: A Retrospective Cohort Study - Liu, Tianjiao; Wen, Li; Huang, Shuai; Han, Ting-li; Zhang, Lan; Fu, Huijia; Li, Junnan; Tong, Chao; Qi, Hongbo; Saffery, Richard; Baker, Philip N.; Kilby, Mark D. (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: To investigate the metabolomic perturbations caused by twin-twin transfusion syndrome and the metabolic changes associated with fetoscopic laser coagulation in both placental tissue and cord plasma, as well as to investigate the differential metabolites pertinent to the varying fetal outcomes, including hemodynamic status, birthweight and cardiac function, of live-born babies. Methods: Placental tissue and cord plasma samples from normal term or uncomplicated preterm-born monochorionic twins and those complicated by twin-twin transfusion syndrome treated with or without fetoscopic laser coagulation were analyzed through high-performance liquid chromatography metabolomic profiling. Sixteen comparisons of different cotwin groups were performed. Partial least squares–discriminant analysis, metabolic pathway analysis, biomarker analysis and Spearman correlation analysis were conducted based on the differential metabolites to determine the potential biomarkers in different comparisons and metabolites that are pertinent to neonatal birthweight and left ventricular ejection fraction. Results: These metabolomic investigations showed that the cord plasma metabolome has a better performance in discriminating fetuses among different hemodynamic groups than placental tissue. The metabolic alteration of twin-twin transfusion syndrome in these two types of samples centers on fatty acid and lipid metabolism. The fetoscopic laser coagulation procedure improves the metabolomic change brought by this syndrome, making the metabolomes of the treated group less distinguishable from those of the control and preterm birth groups. Certain compounds, especially lipids and lipid-like molecules, are noted to be potential biomarkers of this morbid disease and pertinent to neonatal birthweight and ejection fraction. Conclusions: Fetoscopic laser coagulation can ameliorate the metabolomic alteration caused by twin-twin transfusion syndrome in placental tissue and cord plasma, which are involved mainly in fatty acid and lipid-like molecule metabolism. Certain lipids and lipid-like molecules are helpful in differentiating cotwins of different hemodynamic statuses and are significantly correlated with neonatal birthweight or ejection fraction.